In-house validation of an RNA/DNA co-extraction strategy for body fluid identification/STR profiling and application to forensic casework. (December 2015) - Jucker, R.; Sulzer, A.; Voegeli, P.; Haas, C.; Kratzer, A.
Abstract: In the course of an in-house validation of an RNA/DNA co-extraction strategy at least two EDNAP (European DNA Profiling Group) mRNA markers per body fluid were combined into a 12plex. The 12plex should serve as a screening tool, which supplements DNA and presumptive test results. Based on the 12plex results body fluid specific EDNAP multiplexes were used for further confirmation. From the validation and the application of this method to challenging forensic casework samples we present the positive and negative experiences.